EDUCATIONAL CHALLENGES: FACTORS CAUSING IDENTITY CRISIS AMONG GENERATION Z - Ad Dauwi, Anastya Basyith; Yohamintin, Yohamintin; Dhielfitri, Gianluigi Maulana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the factors that cause identity crisis among Generation Z. This research uses a qualitative method with a phenomenological approach. The informants in this study consisted of 6 junior or senior high school students who experienced an identity crisis, 2 junior or senior high school teachers, and 2 parents of students located in Bekasi City and DKI Jakarta. Data analysis in this study used Milles and Hubermen's theory through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Generation Z students experience identity crisis due to two factors, namely internal factors which include inadequate emotion control and insecurity, and external factors which include non-supportive family background, social pressure, and the influence of social media.